Taxonomy of neopasiphaeine bees: review of Tetraglossula Ogloblin, 1948 (Hymenoptera: Colletidae) - Almeida, Eduardo A. B.; Gibran, Nadia S. (Zootaxa, 2017)
Tetraglossula ranges from southern Pará state, Brazil, through central South American (occurring in different biomes: Cerrado savanna, Chaco, and Atlantic forest) southward to the Pampa reaching the province of Buenos Aires, Argentina. Hitherto, four species have been recognized in Tetraglossula Ogloblin, 1948: T. anthracina (Michener, 1989); T. bigamica (Strand, 1910); T. deltivaga Ogloblin, 1948; and T. fucosa (Michener, 1989). Herein, we transfer Bicolletes franki Friese, 1908 to Tetraglossula, and one new species is described: Tetraglossula meloi Almeida & Gibran, sp.n. An identification key is provided for the resulting six species now recognized in Tetraglossula.